Automated Returns Management and Reverse Logistics in SAP - Anasuri, Sunil; Pappula, kiran Kumar (American International Journal of Computer Science and Technology, 2025)
Modern supply chains are significantly influenced by reverse logistics and returns management. The snowball effect that has resulted from the proliferation of online purchasing and the ease with which customers can request returns has compelled businesses and their customers to ensure that they have well-organized and automated return systems. This article is about returns management and reverse logistics with computers in a SAP environment–the subject however is restricted to these three SAP functionalities: SAP S/4HANA EWM and CRM toolsetne Mechanism for Returns: Using such SAP technologies (not yet fully automated) as processing credit memos or changing inventory, managing reverse logistics and permission Continuing Return Material Authorizations (RMA)–this report on how electronic technology has introduced new concepts into returns management looks at past difficulties and changing technologies in the future.It describes some of the benefits of automation in SAP, and how happy customers will purchase more products from you while also reducing your staff’s workload. These benefits include improved operational efficiency–no longer having to return items cross country-andespecially lower costs The action returns automation policies was brought to the institutions which pioneered it together leverage points